Intact piRNA pathway prevents L1 mobilization in male meiosis - Newkirk, Simon J. (Proc Natl Acad Sci U S A, 2017)
The PIWI-interacting RNA (piRNA) pathway is essential for retrotransposon silencing. In piRNA-deficient mice, L1-overexpressing male germ cells exhibit excessive DNA damage and meiotic defects. It remains unknown whether L1 expression simply highlights piRNA deficiency or actually drives the germ-cell demise. Specifically, the sheer abundance of genomic L1 copies prevents reliable quantification of new insertions. Here, we developed a codon-optimized L1 transgene that is controlled by an endogenous mouse L1 promoter. Importantly, DNA methylation dynamics of a single-copy transgene were indistinguishable from those of endogenous L1s. Analysis of Mov10l1(−/−) testes established that de novo methylation of the L1 transgene required the intact piRNA pathway. Consistent with loss of DNA methylation and programmed reduction of H3K9me2 at meiotic onset, the transgene showed 1,400-fold increase in RNA expression and consequently 70-fold increase in retrotransposition in postnatal day 14 Mov10l1(−/−) germ cells compared with the wild-type. Analysis of adult Mov10l1(−/−) germ-cell fractions indicated a stage-specific increase of retrotransposition in the early meiotic prophase. However, extrapolation of the transgene data to endogenous L1s suggests that it is unlikely insertional mutagenesis alone accounts for the Mov10l1(−/−) phenotype. Indeed, pharmacological inhibition of reverse transcription did not rescue the meiotic defect. Cumulatively, these results establish the occurrence of productive L1 mobilization in the absence of an intact piRNA pathway but leave open the possibility of processes preceding L1 integration in triggering meiotic checkpoints and germ-cell death. Additionally, our data suggest that many heritable L1 insertions originate from individuals with partially compromised piRNA defense.